A Summary of Wellbore Fluid Accumulation and Drainage Gas Production Technology in Gas Wells. Issue 1 (January 2021) - Chen, Ming; Sun, Junyi; Gao, Ersi; Tian, Haonian
Abstract: The problem of fluid accumulation in the wellbore of a gas well is an important factor that affects the efficiency of gas production. If the fluid accumulation is serious, the production of the gas well will decrease, and then the gas well will be flooded and stop production. It is necessary to drain the wellbore fluid to the surface in time. This article analyzes the causes and diagnostic methods of wellbore fluid accumulation, and introduces conventional fluid drainage technology such as optimization of tubing, bubble drainage, gas lift fluid drainage and mechanical fluid drainage, aiming at improving the liquid carrying capacity of gas wells and improving the gas recovery efficiency of gas wells. Examples illustrate the feasibility of drainage technology and restore normal production of gas wells.